Topological concepts and their relation to engineering thinking among middle school students - et. al., Saleem Abdul Munem Abdul Ameer Turk, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to investigate the topological concepts for intermediate stage students, engineering thinking among intermediate stage students, and the relationship between topological concepts and engineering thinking for intermediate stage students. The research sample consisted of (220) students from the first intermediate class / first Rusafa, where verification of validity and reliability were conducted for the topological test concepts as a first tool and a test for engineering thinking as a second tool. Accordingly, the two tests were ready to be applied to the basic sample and in their final form, which the topological concepts test items reached (16) items, while the engineering thinking test items reached (18) items, Furthermore, the statistical package for social sciences (SPSS) was applied to analyze the research results. and the results showed that first intermediate class students possess topological concepts and engineering thinking that exceeds the assumption average of the test and that there is a positive relation between topological concepts and engineering thinking. Finally, the researchers presented a set of proposals and recommendations based on the results of the study